2022
DOI: 10.3390/ceramics5040079
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of NiO/YSZ-Based Anodes for Solid Oxide Fuel Cells by Hybrid 3D Inkjet Printing and Laser Treatment

Abstract: An anode for solid oxide fuel cells (SOFCs) was fabricated using 3D inkjet printing and layer-by-layer laser treatment of compositions based on the NiO/YSZ system followed by thermal sintering. The samples were characterized by scanning electron microscopy and X-ray phase analysis. The study of the morphology of the as-prepared samples revealed the presence of both interlayer macroporosity and intralayer microporosity, which depends on the laser exposure during laser treatment. The use of graphite directly add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Analysis of the percentile values D75 showed (Figure 2b) that the optimum milling and homogenization time of the NiO/10YSZ composite (60:40) is 1 h. A further increase in the milling time almost does not affect the average particle size. In our earlier study [35], it was shown that the introduction of a pore former is required to achieve the optimum porosity of the anode support. Figure 3 shows the dependence of the dynamic viscosity on the shear rate for an organic binder and for pastes in the absence and the presence of the pore-former graphite (20 wt.%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the percentile values D75 showed (Figure 2b) that the optimum milling and homogenization time of the NiO/10YSZ composite (60:40) is 1 h. A further increase in the milling time almost does not affect the average particle size. In our earlier study [35], it was shown that the introduction of a pore former is required to achieve the optimum porosity of the anode support. Figure 3 shows the dependence of the dynamic viscosity on the shear rate for an organic binder and for pastes in the absence and the presence of the pore-former graphite (20 wt.%).…”
Section: Resultsmentioning
confidence: 99%
“…To print NiO/YSZ anodes, a hybrid laboratory inkjet 3D printer with the possibility of laser post-treatment of layers was used, which can use various dispensing systems for low-viscosity and high-viscosity compositions to control the layer thickness and shape of the final sample [35]. All experiments on printing were carried out using a pneumatic pulse valve with a nozzle diameter of 0.25 mm (Nordson Corporation, Erkrath, Germany; Westlake, OH, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation